2018
DOI: 10.3389/fimmu.2018.00928
|View full text |Cite
|
Sign up to set email alerts
|

CD32-Expressing CD4 T Cells Are Phenotypically Diverse and Can Contain Proviral HIV DNA

Abstract: Efforts to both characterize and eradicate the HIV reservoir have been limited by the rarity of latently infected cells and the absence of a specific denoting biomarker. CD32a (FcγRIIa) has been proposed to be a marker for an enriched CD4 T cell HIV reservoir, but this finding remains controversial. Here, we explore the expression of CD32 on CD3+CD4+ cells in participants from two primary HIV infection studies and identify at least three distinct phenotypes (CD32low, CD32+CD14+, and CD32high). Of note, CD4 neg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 45 publications
10
53
1
Order By: Relevance
“…We previously reported partial enrichment for HIV DNA in CD4 T cells associating with CD32 in some individuals, 18 prior to the finding that CD32 + CD4 + flow cytometric events comprised doublets. We therefore wished to explore the phenotype and potential physiological-versus artefactual-relevance of T cells engaged in doublet formation, whether they were also present in GALT, and any possible association with the GALT HIV reservoir.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…We previously reported partial enrichment for HIV DNA in CD4 T cells associating with CD32 in some individuals, 18 prior to the finding that CD32 + CD4 + flow cytometric events comprised doublets. We therefore wished to explore the phenotype and potential physiological-versus artefactual-relevance of T cells engaged in doublet formation, whether they were also present in GALT, and any possible association with the GALT HIV reservoir.…”
Section: Introductionmentioning
confidence: 85%
“…Recent work suggesting that CD32a (a low-affinity IgG receptor not generally expressed on T cells 10 ) was a specific marker for latent HIV infection 11 was initially supported by studies showing that CD32 may be found on cells that are transcriptionally active, and was associated with HIV DNA levels in some patients. [12][13][14][15][16][17][18][19] However, the finding that CD32 co-expression with CD4 is predominantly due to T-cell-B-cell doublets 17 likely undermines the argument that CD32 is a definitive marker of latency.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the expression of CD32a has been reported as a potential marker of memory CD4 + T cells harboring a replication-competent latent virus in aviremic patients under ART (Descours et al, 2017;Darcis et al, 2019). The role of CD32a as a cellular marker of HIV-1 reservoirs has been the subject of several works Martin et al, 2018;Osuna et al, 2018;Thornhill et al, 2019). A complete study presented at CROI by Darcis et al (CROI 2019, Poster 346 -CD32 + CD4 + T cells are enriched in HIV-1 DNA) showed that active CD4 + T cells co-expressing HLA-DR and CD32a are highly enriched with HIV-1 DNA.…”
Section: Markers Of Latently-infected Cd4 + T Cellsmentioning
confidence: 99%
“…Recently, CD32+ CD4 T cells have been proposed to be a major host of the LR, whereby selection of this cell population resulted in significant enrichment of inducible provirus (Descours et al, 2017;Darcis et al, 2020). Conflicting reports, however, have failed to replicate this finding and the contribution of CD32+ CD4 T cells to HIV-1 persistence and rebound remains controversial (Abdel-Mohsen et al, 2018;Badia et al, 2018;Bertagnolli et al, 2018;Martin et al, 2018;Osuna et al, 2018;Pérez et al, 2018). Nonetheless, the use of CD32 as a marker of latent infection is a topic of particular interest and may provide a mechanism by which the LR can be specifically targeted.…”
Section: The Hosts Of the Reservoirmentioning
confidence: 99%